Analysis of mechanisms of phytoplankton layer formation, maintenance and dissipation in a tropical reservoir (2017)
The mechanisms of thin phytoplankton layers development were investigated in the tropical La Fe reservoir in terms of the balance between convergence processes acting to thin the layers and turbulent diffusion acting to dissipate them. Our approach included the analysis of field data collected in a field campaign during September 2012, the calibration of the hydrodynamic and ecological model ELCOM-CAEDYM, and the application of a scaling analysis in order to understand and define the processes involved in the formation, maintenance and dissipation of the observed thin layers in the reservoir. Based on the scaling analysis applied to identify the mechanisms participating in the layering process, we defined in situ growth as the primarily mechanism involved in the formation of the layers. The influx of nutrients due to horizontal intrusions and vertical turbulent fluxes influenced this mechanism. Other analyzed mechanisms were convergent swimming and buoyancy of phytoplankton cells. The stratification of the water column together with the dissipation rates responsible to the turbulence around the layers defined local region with favorable conditions to the development of thin layers. Further studies are needed in order to characterize more precisely the mechanisms involved in the development of phytoplankton layers in this reservoir and other environments.